2020
DOI: 10.3390/antiox9100987
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Protein Methionine Oxidation in Response to Hydrogen Peroxide Treatment–Ex Vivo Versus In Vitro: A Computational Insight

Abstract: Methionine oxidation plays a relevant role in cell signaling. Recently, we built a database containing thousands of proteins identified as sulfoxidation targets. Using this resource, we have now developed a computational approach aimed at characterizing the oxidation of human methionyl residues. We found that proteins oxidized in both cell-free preparations (in vitro) and inside living cells (ex vivo) were enriched in methionines and intrinsically disordered regions. However, proteins oxidized ex vivo tended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This is consistent with our previous finding that Met-sulfoxide and 5-oxoproline declined during the aggravation of IL1-β-induced HGF inflammation by TiO 2 nanoparticles ( Supplementary Figure S2A,B , cited from [ 15 ]). Since Met-sulfoxide [ 23 , 24 , 25 ] and 5-oxoproline [ 26 , 27 , 28 ] are well-known markers reflecting oxidative stress, SE might have induced the cells to fight against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our previous finding that Met-sulfoxide and 5-oxoproline declined during the aggravation of IL1-β-induced HGF inflammation by TiO 2 nanoparticles ( Supplementary Figure S2A,B , cited from [ 15 ]). Since Met-sulfoxide [ 23 , 24 , 25 ] and 5-oxoproline [ 26 , 27 , 28 ] are well-known markers reflecting oxidative stress, SE might have induced the cells to fight against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that every amino acid has a characteristic sequence environment in proteins 41 , 54 . In previous works, we have analyzed the sequence environment (10 residues on each side) around methionine residues in human proteins 42 , 43 , 55 . Thus, and just based on methionine residues, the human proteome can be characterized by a matrix, M , whose elements (m ij ) provide the absolute frequency of the amino acid i at the position j in the environment of methionine residues (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The species vector space It has been shown that every amino acid has a characteristic sequence environment in proteins 39,46 . In previous works, we have analyzed the sequence environment (10 residues on each side) around methionine residues in human proteins 40,41,47 . Thus, and just based on methionine residues, the human proteome can be characterized by a matrix, M, whose elements (m ij ) provide the absolute frequency of the amino acid i at the position j in the environment of methionine residues (Figure 1A).…”
Section: Methodsmentioning
confidence: 99%